AB0635 Anti-phospholipid antibodies in lupus myocarditis. (12th June 2018) - Dhir, V.; Gawalkar, A.; Ahluwalia, J.; Bahl, A.; Sharma, S.; Sharma, A.; Jain, S.
Abstract : Background: Myocarditis in lupus is an uncommon clinical manifestation, with unknown pathogenesis.( 1 Suggested etiologies includes Immune-complexes, cell mediated damage and anti-phospholipid antibodies. The latter may affect the myocardial function microthrombi in cardiac vessels or direct cytotoxicity.( 2 Previously, small studies have suggested an association between antiphospholipid tests as myocarditis. Objectives: To evaluate whether myocarditis in SLE is associated with antiphospholipid positivity. Methods: This was a cross-sectional study in which patients fulfilling SLICC criteria 2012 for SLE or Alarcon Segovia criteria for MCTD were included after consent. Patients were recruited as 'Cases' if they had myocarditis/cardiomyopathy defined by poor generalised contractility and/or dilation of all chambers nad/or reduced ejection fraction on echocardiography without any obvious cause. Those with regional wall motion abnormalities or pulmonary artery hypertension (moderate or severe) were excluded. Controls were age (±2.5 years) and disease duration (±25%) matched patients of SLE without any abnormality on echocardiography. Serum titers of anticardiolipin antibodies and b2 GP1 (both IgG and IGM) were measured by commercial ELISA kit. Lupus anticoagulant was detected by Dilute Russell Viper Venom Test (dRVVT) with both screening (prolonged) and confirmation steps (shortening on higher phospholipid content, ratio >1.2) on doubly centrifuged, platelet poor plasma. Proportions were compared using chi-square test (or Fischers exact test) and continous variables by Mann-Whitney U test. Results: A total of 51 patients were recruited in this study that included 21 cases and 30 controls. All had SLE, except 1 case was of MCTD (among cases). There was no difference in mean (±SD) age (33.3±14.7, 32.8±12.4 years, p=0.9) or median (interquartile range) disease duration (30, 8–38 25 (13.5–45) months, p=0.6) between groups. Mean ejection fraction of Cases was 31.7% (±9.3%) while that of Controls was 55.7% (±1.7%) (p<0.001). There were no significant differences between proportion of Cases (42.9%) and Controls (40%) with positive anti-phospholipid tests (p=0.7). The majority had positive anticardiolipin antibodies, followed by b2 GP1, and lupus anticoagulant was positive in only two in each group (figure 1). Among 9 Cases positive at baseline, 6 patients could be re-tested (2 expired and 1 was lost), out of which 3 had persistent positivity. Out of 12 Controls positive once, 8 could be retested (1 expired and 3 were lost), with 1 being persistently positive. There was no signficiant difference in persistent positivity between groups. (p=0.3). Conclusions: This study did not find any signficant association between antiphospholipid antibodies (single time or persistent) with cases of lupus myocarditis. References: [1] Doria A, Iaccarino L, Sarzi-Puttini P, Atzeni F, Turriel M, Petri M. Cardiac involvement in systemic lupus erythematosus. Lupus. 2005;14(9):683–6. [2] Bidani AK, Roberts JL, Schwartz MM, Lewis EJ. Immunopathology of cardiac lesions in fatal systemic lupus erythematosus. The American journal of medicine. 1980;69(6):849–58. Disclosure of Interest: None declared